End of Meeting Report - ISPC 14 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2016)
The fourteenth meeting of the ISPC was held from the 14-16 September 2016 at ICRISAT Headquarters, Patancheru, India.